Жертовники з черепами в уроч. Царина Більського городища (до суті ритуалу) - Вертієнко, Г.В. (Археологія, 2017)
Надано опис групи жертовників із людськими черепами, відкритих на зольниках в уроч. Царина на Великому Більському городищі. Пропонується інтерпретація обряду цих жертвоприношень через призму індійського ритуалу (агнічаяни). The issue of ritual usage of human heads (skulls) in the altars discovered on the ashpits 1 and 3 at the Tsaryna stow at Great Bilske hill-fort is discussed in the paper. Five such objects were investigated. The most archaic altar is dated back to the 7th century BC (altar 1, ashpit 3) and the rest are dated by the 5th century BC (altar 2, ashpit 3; altar 3, ashpit 3; altar 2, ashpit 1; hole 6, ashpit 1). The essential difference between them lays in design features and placing of the skulls. In the archaic altar, two skulls were built into the basement of the structure which represented a clay cone. In later altars, which predominantly had a shape of a low hill constructed on subsoil, skulls were placed in the upper part of cultic objects. V.P. Belozor’s opinion that the archaic altar 1 could be a backbone object (a sanctuary?) at the ashpit 3 appears to be reasonable. This altar’s structure reminds the design of Agni altar in Agnicayana rite in which the head of a sacrificed person was placed in the structure’s basement. Proceeding from the fact that economic activity at this ashpit was closely connected with metallurgical production, the ritual itself, as well as in a case with the Indian equivalent, could be devoted to a cult of fire and have a similar semantic capacity. В статье рассмотрена проблема ритуального использования человеческих голов (черепов) в жертвенниках, открытых на зольниках 1 и 3 в уроч. Царина Большого Бельского городища. Было исследовано пять таких объектов. Наиболее архаичный жертвенник датируется VII в. до н. э. (жертв. 1, зол. 3), остальные — V в. до н. э. (жертв. 2, зол. 3; жертв. 3, зол. 3; жертв. 2, зол. 1; яма 6, зол. 1). Существенное отличие между ними состоит в конструктивных особенностях и в размещении черепов. В архаическом жертвеннике два черепа были вмонтированы в фундамент сооружения, представлявшего собой глиняный конус. В более поздних жертвенниках, преимущественно имевших форму невысокого холма, сооружавшегося на материковой глине, черепа размещались в верхней части культовых объектов. Представляется обоснованным мнение В.П. Белозора, что архаический жертвенник 1 мог быть системообразующим объектом (святилищем?) на зольнике 3. Конструкция этого жертвенника напоминает устройство алтаря Агни по ритуалу агничаяны, в котором голову принесенного в жертву человека была помещена в фундаменте сооружения. Исходя из того, что хозяйственная деятельность на зольнике была тесно связана с металлургическим производством, сам ритуал, как и в случае с индийским эквивалентом, мог быть посвящен культу огня и иметь схожую семантическую нагрузку.